PENGEMBANGAN KAPASITAS MASYARAKAT DI DESA TUMALUNTUNG KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA MELALUI BADAN USAHA MILIK DESA - LUMEMPOUW, SALLY; RURU, JOORIE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2021)
The development of community capacity in Tumaluntung village through the Village Owned EnterprisesInstitution (BUMDes), it seems that there are still indications of problems. such as the lack of publicawareness in managing the funds they get from BUMDes and the lack of guidance or training from theBUMDes Institution for people who use the BUMDes program, so there is no visible change in CommunityCapacity Development in Tumaluntung Village. This study uses a qualitative approach. Data obtained frominterviews, observations and documents. Data analysis was carried out through data reduction, datapresentation, and conclusion drawing. The findings of this study are that the development of communitycapacity in Tumaluntung Village through the existing BUMDes from the aspect of human resources relatedto: the dimensions of knowledge and skills as well as motivation. The management of the Village-OwnedEnterprises Institution in the village of Tumaluntung should pay more attention to the community usingBUMDes and also people who do not use BUMDes, and create programs to motivate the community tocreate Community Capacity Development, as well as create programs to provide training to the community.in order to increase the knowledge and skills of the community.Kay Word : Capacity Building, Village Owned Enterprises